Positive and less positive outcomes of corporate culture - Alvesson, Mats, 1956- ([London] : SAGE, 2016)
This case presents a field study of a Swedish computer consultancy company (CCC), in terms of the organizational structure and culture of the firm, social relations with other companies, and innovative ideas that led to its growth. The case study also illustrates the complexities of performance management and the potential significance of cultural meanings and values for corporate results.
Originally Published in: Alvesson, M. (2012). Positive and Less Positive Outcomes of Corporate Culture. A Case Study. In Understanding organizational culture (2nd ed., pp. 65-70). London: SAGE Publications Ltd. ISBN: 9780857025586.
Description based on online resource; title from home page (viewed on April 26, 2016).
Keywords: elektronické knihy; electronic books; Corporate culture -- Case studies; Organization -- Case studies